Saltwater : A Theory of Thought Forms - Christov-Bakargiev, Carolyn; Colomina, Beatriz; Deutscher, Penelope; Ettinger, Bracha; Groys, Boris; Irvine, William; Örer, Bige; Niermann, Ingo; Martinez, Chus; Pamuk, Orhan; Peakall, Jeffrey; Rigolo, Pietro; et al. (Istanbul : Istanbul Foundation for Culture and Arts, 2015)
Alÿs, Francis ; Adnan, Etel ; Aivazian, Haig ; Ah Kee, Vernon ; Algün Ringborg, Meric ; Anastas, Ayreen ; Ang, Song-Ming ; Anselmo, Giovanni ; Atkins, Ed ; Balassanian, Sonia ; Benglis, Lynda ; et al.
In scope of the 14th Istanbul Biennial, Istanbul, 5.9.2015-1.11.2015
Catalogue
kunstcatalogus